In vitro inhibition of matrix metalloproteinases, invasion and growth of Fanconi anemia human FANCA and FANCC lymphoblasts by nutrient mixture - Roomi, M.W.; Bhanap, B.; Roomi, N.W.; Niedzwiecki, A.; Rath, M. (Experimental Oncology, 2014)
Aim: Fanconi anemia is a rare genetic disorder with high propensity for development of cancers, such as aplastic anemia, leukemia and head and neck cancers. Collagen digesting matrix metalloproteinase (MMP) enzymes have been implicated in for their role in various malignancies and to promote metastasis. Biological agents that prevent extracellular matrix digestion by the MMPs have been shown to be promising therapeutic approaches to cancer. In this study, we investigated effects of a nutrient mixture (NM) containing, ascorbic acid, lysine, proline and green tea extract, on human FANCA and FANCC lymphoblasts for viability, MMP secretion and invasion. Methods: Human FANCA lymphoblasts GM13022 and HCS536 were challenged with NM at concentration range within 10–1000 µg/ml. Cell toxicity was assessed by Trypan blue dye exclusion test. Invasion was evaluated through Matrigel and gelatinase zymography for MMP activity. Results: NM was toxic in dose dependent mode to HCS536 cells but not to GM13022 cells. GM13022 cells but not HCS536 cells exhibited MMP-9 secretion, which was inhibited by NM. Matrigel invasion was inhibited in HCS536 cells at 100 and 500 µg/ml by 27% and 93%, respectively. In GM13022 cells, the NM showed completely blocked Matrigel invasion at 500 µg/ml. Conclusion: NM inhibited MMP secretion and Matrigel invasion in FANCA and inhibited invasion and induced toxicity in FANCC lymphoblasts. These results suggest that the NM may have therapeutic potential in Fanconi anemia associated neoplasia. Key Words: Fanconi anemia, nutrient mixture, MMP, Matrigel invasion.